(untitled) (National Administration Journal, 2020)
The essay shows the relationship of the Bolivian Model of Excellence with the Ibero-American Model and how it has been modified to adapt to the Living Well policy proposed by the government. For this the models were compared and an investigation was carried out on the participation of the organizations in the excellence awards during the last 7 years. One of the main findings is the lack of interest of companies in the Bolivian Model due to the lack of disclosure, its alignment towards the results of society, departing from the expectations of interest groups and the distance between private companies with the initiatives of the expresident’s government. The results are innovative, because, in Bolivia, there are still no measures to analyze and improve this situation.